Dilatation or no dilatation of the cervix during cesarean section (Dondi Trial): a randomized controlled trial - Kirscht, Jade; Weiß, Christel; Nickol, Jana; Berlit, Sebastian; Tuschy, Benjamin; Hoch, Benjamin; Trebin, Amélie-Verena; Große Steffen, Thomas; Sütterlin, Marc; Kehl, Sven (Archives of gynecology and obstetrics, 2017)
Purpose To assess the effects of mechanical dilatation of the cervix during cesarean section on postoperative morbidity.MethodsA total of 447 women with elective cesarean section were included in the Dondi trial (Dilatation or no dilatation of the cervix during cesarean section). The primary outcome measure of this randomized controlled trial was postpartum hemorrhage (PPH) within 6 weeks. Infectious morbidity (puerperal fever, endometritis, wound infection, and urinary tract infection), blood loss (need for blood transfusion or change in hemoglobin levels), and operating time were also evaluated.ResultsThe rate of PPH within 6 weeks was not different between the two groups [dilatation group: 5 (2.4 %), no dilatation group: 3 (1.2 %), p = 0.479]. Infectious morbidity, blood loss, and operating time were not diverse as well. The only significant difference between the two groups was the rate of retained products of conception with fewer cases after cervical dilatation (0 versus 6.2 %, p < 0.001).Conclusions Dilatation of the cervix during cesarean section compared with no dilatation of the cervix did not influence the risk of postpartum hemorrhage. However, there were fewer cases with retained products of conception after dilatation.